Expression of connexin 43 protein in cardiomyocytes of heart failure mouse model - Liu, Shaoyan; Lan, Yang; Zhao, Yun; Zhang, Qianyu; Lin, Tzuchun; Lin, Kaibin; Guo, Junjie; Yan, Yan (Frontiers in Cardiovascular Medicine, 2022)
Heart failure (HF) is the end stage of various cardiovascular diseases, with high morbidity and mortality, and is associated with poor prognosis. Aortic valve disease is one of the leading causes of heart failure, it is mainly manifested by progressive stenosis of the aortic valve, resulting in increased left ventricular load, ventricular hypertrophy, and ultimately ventricular dysfunction and heart failure. Early assessment of the degree of cardiomyopathy and timely intervention is expected to improve patients' cardiac function and delay or even avoid the occurrence of HF. The Wnt signaling pathway is mainly involved in the regulation of myocardial insufficiency after valve stenosis. Connexin 43 protein (Cx43) is an important target of Wnt signaling pathway that form gap junction structures and widely distributed in various organs and tissues, especially in the heart. In order to specifically label Cx43 in vivo, we established a new Cx43-BFP-GFP mouse model that have two loxp sites on both sides of the tagBFP-polyA box, which can be removed by Cre recombination. This double-reporter line provides us with a powerful genetic tool for determining the area, quantity, spatial distribution and functional status of Cx43 as well as indicating changes in electrical conduction between cells under steady state or disease states.